The epigenome in pluripotency and differentiation. (February 2014) - Thiagarajan, Rathi D; Morey, Robert; Laurent, Louise C
The ability to culture pluripotent stem cells and direct their differentiation into specific cell types in vitro provides a valuable experimental system for modeling pluripotency, development and cellular differentiation. High-throughput profiling of the transcriptomes and epigenomes of pluripotent stem cells and their differentiated derivatives has led to identification of patterns characteristic of each cell type, discovery of new regulatory features in the epigenome and early insights into the complexity of dynamic interactions among regulatory elements. This work has also revealed potential limitations of the use of pluripotent stem cells as in vitro models of developmental events, due to epigenetic variability among different pluripotent stem cell lines and epigenetic instability during derivation and culture, particularly at imprinted and X-inactivated loci. This review focuses on the two most well-studied epigenetic mechanisms, DNA methylation and histone modifications, within the context of pluripotency and differentiation.